Unified model of field assisted sintering and related phenomena. (February 2020) - Narayan, J.
Abstract: Critical elements of the model are temperature-assisted generation of free electrons, field-assisted transport and trapping of free electrons to generate defects, segregation of defects to dislocations and grain boundaries through elastic and electrostatic interactions, and creation of percolation paths along grain boundaries. There is a critical electric field required to establish these percolation paths, where free electrons-defects-free electrons bootstrapping avalanche occurs, leading to selective Joule heating and localized melting to achieve near theoretical density. The critical field for percolation is a function of microstructure, temperature and time (incubation period), and it is much higher for single crystals than polycrystalline materials.